2020
DOI: 10.1136/annrheumdis-2020-217984
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for hospital admissions related to COVID-19 in patients with autoimmune inflammatory rheumatic diseases

Abstract: ObjectivesTo describe patients with autoimmune inflammatory rheumatic diseases (AIRD) who had COVID-19 disease; to compare patients who required hospital admission with those who did not and assess risk factors for hospital admission related to COVID-19.MethodsAn observational longitudinal study was conducted during the pandemic peak of severe acute respiratory syndrome coronavirus 2 (1 March 2020 to 24 April). All patients attended at the rheumatology outpatient clinic of a tertiary hospital in Madrid, Spain … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
104
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(125 citation statements)
references
References 22 publications
(26 reference statements)
16
104
4
1
Order By: Relevance
“…10,28 The same report indicated that 32% of social media users were female, whereas the published cohorts of patients with CRD reported a female prevalence of 72%. 10,30 Around 60% of our population were from 3 countries: Iraq, KSA, and Egypt. This high contribution reflects the large populations in these countries.…”
Section: Discussionmentioning
confidence: 99%
“…10,28 The same report indicated that 32% of social media users were female, whereas the published cohorts of patients with CRD reported a female prevalence of 72%. 10,30 Around 60% of our population were from 3 countries: Iraq, KSA, and Egypt. This high contribution reflects the large populations in these countries.…”
Section: Discussionmentioning
confidence: 99%
“…This finding that indicates the increased need for rheumatologists during the COVID-19 pandemic may be attributable to two factors: (a) patients with a rheumatic disease and/or receiving immunosuppressive treatments wanted to consult rheumatologists on their disease/treatments [30]; (b) patients consult rheumatologists on properties of several anti-inflammatory and immunomodulatory drugs that are being used in the treatment of COVID-19 because rheumatologists are experts in the use of these drugs [1,7]. Rheumatic patients may be at a higher risk of receiving COVID infection with worse outcomes, as many of them tend to be susceptible from their underlying rheumatic disease or immunocompromised due to their treatment [9][10][11][12][13][14][15][16]. Thus, this pandemic has put great responsibility on the shoulders of the rheumatologists for caring for this vulnerable patient group.…”
Section: Discussionmentioning
confidence: 99%
“…Since rheumatologists have substantial knowledge in the benefits and adverse effects of these drugs as well, rheumatologists are playing a significant role in this pandemic. Besides fighting COVID-19, the rheumatologists also have an essential role in caring for their rheumatic patients who may express concerns about their potential increased risk of acquiring COVID-19 infection due to their underlying disease itself and any immunosuppressive treatments they may be on [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Since excessive in ammatory response is known to be associated with severe COVID-19, it is of particular interest to nd out whether a speci c IRD diagnosis in uences COVID-19 outcome. Two studies with a relatively small number of patients found no association between IRD diagnoses and a worse outcome [11,12] and two other studies showed a higher risk for severe COVID-19 among patients with diagnoses other than in ammatory arthritis such as connective tissue diseases, vasculitis and sarcoidosis [13,14].…”
Section: Discussionmentioning
confidence: 99%